The culture of prewedding photography in the religious and social perspectives of the Lungge Village community, Temanggung - Muh. Baehaqi; *, Ahmad Luthfi Aziz; Zaenal Arifin; Syahdara Anisa Makruf (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study examines the practice of prewedding photography in Lungge Village and analyzes it from the perspectives of Islamic law and culture. Prewedding photography, as a modern cultural phenomenon, has emerged alongside technological advancement and globalization and has become part of the process leading to marriage for some members of society. This research employs a qualitative approach using interviews and literature review to explore the background, objectives, and views of the community and religious scholars regarding prewedding photography. The findings indicate that the people of Lungge Village engage in prewedding photography for various purposes, including documentation, public announcement, complementing wedding invitations, and adapting to contemporary trends. Nevertheless, prewedding photography is not regarded as obligatory or recommended, but rather as optional. From the perspective of Islamic law, scholars from Nahdlatul Ulama, Muhammadiyah, and local religious figures generally consider prewedding photography to be mubāḥ (permissible). However, its legal status may change to ḥarām (prohibited) if the practice violates Islamic principles, such as exposing awrah, physical contact, khalwat (seclusion), or intimate poses between prospective spouses prior to a valid marriage contract. Therefore, prewedding photography is viewed as conditional and must be carried out with caution (iḥtiyāṭ), in accordance with Islamic ethics, and with objectives that do not lead to harm. This study concludes that prewedding photography, as a product of modern cultural acculturation, may be accepted in Islam as long as it does not contradict Islamic values and continues to uphold the sanctity of marriage as an act of worship.